EFIKASI DIRI DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK - Hanifah Nur Jannah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of self-efficacy and entrepreneurship education on students' entrepreneurial interest. The study used a survey method with a quantitative approach. The population in this study were all class XI students majoring in Marketing at SMK Negeri 1 Tasikmalaya which amounted to 140 people, with a saturated sample technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the analysis show that self-efficacy has a positive and significant effect on entrepreneurial interest, with a t value of 2.565 and a significance of 0.011. Entrepreneurship education also has a positive and significant effect on entrepreneurial interest, with a t value of 6.704 and a significance of 0.000. Simultaneously, self-efficacy and entrepreneurship education have a positive and significant effect on students' entrepreneurial interest, with a calculated F value of 36.277 and a significance of 0.000 and with an R2 value of 34.6%. These findings confirm that strengthening self-efficacy and optimizing entrepreneurship education programs have an important role in increasing entrepreneurial interest among vocational students, especially in the field of marketing.